Intravenous artesunate for severe malaria in travelers, Europe - Zoller, Thomas; Junghanss, Thomas; Kapaun, Annette; Gjørup, Ida; Richter, Joachim; Hugo-Persson, Mats; Mørch, Kristine; Foroutan, Behruz; Suttorp, Norbert; Yürek, Salih; Flick, Holger (Emerging infectious diseases, 2011)
Multicenter trials in Southeast Asia have shown better survival rates among patients with severe malaria, particularly those with high parasitemia levels, treated with intravenous (IV) artesunate than among those treated with quinine. In Europe, quinine is still the primary treatment for severe malaria. We conducted a retrospective analysis for 25 travelers with severe malaria who returned from malaria-endemic regions and were treated at 7 centers in Europe. All patients survived. Treatment with IV artesunate rapidly reduced parasitemia levels. In 6 patients at 5 treatment centers, a self-limiting episode of unexplained hemolysis occurred after reduction of parasitemia levels. Five patients required a blood transfusion. Patients with posttreatment hemolysis had received higher doses of IV artesunate than patients without hemolysis. IV artesunate was an effective alternative to quinine for treatment of malaria patients in Europe. Patients should be monitored for signs of hemolysis, especially after parasitologic cure.
Gesehen am 23.01.2023